ANALISIS RASIO KEUANGAN UNTUK MENGUKUR KINERJA KEUANGAN KOPERASI SERBA USAHA - Sayekti Suindyah Dwiningwarni; Ririn Dwi Jayanti (Fakultas Ekonomi Universitas Islam Darul Ulum Lamongan, 2019)
The motivation of this research is the research of Dwiningwarni et.al (2019) and Shobihin et.al (2019). The research objective is to analyze the Cooperative's financial performance by using Financial Ratio and analysis financial statements. The analytical method used is the comparative method of Financial Ratios , Trend analysis and Common Size. The sampling technique uses systematic sampling. The results showed that 1) From the calculation of the ratio analysis used, the third ratio analysis, namely Liquidity, Profitability, Solvency and Activity showed an unfavorable condition. 2) From the Trend analysis shows that the trend tends to fluctuate up or down. 3) From the Common Size analysis, it shows that the items of assets, liabilities and capital provide figures that are less comparable or can be said to be unhealthy, because the amount of liabilities is greater than assets and capital. This means it can be concluded that the Cooperative's financial condition is not healthy, so there needs to be improved management or management. Improved management not only from the financial side but also from the HR side. One of the causes of unhealthy cooperative financial performance is liquidity ratios, solvency, profitability and activities that show poor and not good results.